Analysis of badminton competitions in 2012 London Olympics - Aydogmus, M.; Arslanoglu, E.; Senel, O. (Turkish Journal of Sport and Exercise, 2014)
In this study, the general analysis of 2012 London Olympics Badminton matches are aimed to be made. In this analysis, the physical characteristics of the Olympic players, the average match and rally durations, the countries which have participated by rally stroke points and the distributions of the medals were studied. The official website of 2012 London Olympics were used as a means of collecting data and during the matches, the results and analysis of a total 189 matches published on this site were recorded and evaluated. The study was carried out by using the data which belong to a total of 170 players (90 women and 80 men) who participated from 52 countries. Descriptive statistical analysis of data (mean, standard deviation, minimum and maximum values, percentage distribution) was done by using SPSS 17.0 for Windows. As a result of this research, the mean total match duration in singles and doubles categories were determined as; for males 45.12±13.24 minutes, 39.37±11.46 minutes, for females 37.7±12.46 minutes, 42.27 ±8.94 minutes respectively. The longest rally mean durations of competitions in man and women singles were respectively 38.4±16.22 seconds, 34.6±8.15 seconds; in men doubles, in women doubles and in mix doubles were respectively 38.18±15.13, 48.16±11.8 and 23.19±9.15 seconds. When the highest rally strokes, with average of 53,39±15,7 strokes, took place in the women doubles, it was followed by women singles (41,39±10,6), men singles (38.66±13.26), men doubles (36.74±12.58) and mix doubles (35.43±8.67). When looked at the data obtained in this study, it is observed that the highest mean match durations are in men singles and the longest mean rally durations and the highest mean rally strokes are in women doubles categories. As a conclusion, according to the 2012 London Olympics analysis, badminton coaches must revise technical, tactical, conditional elements of badminton and they have to prepare special schedules for category properties.